Tanggap Morfofisioligi Beberapa Varietas Kedelai di Lahan Pasang Surut Tipe C - Rinata, Rena; Nurjani, Nurjani; Santoso, Edy (Perkebunan dan Lahan Tropika, 2023)
This research aims to look for the best morphophysiology response   of soybean varieties in the tidal land type C. Research activities conducted in Kalimas Village Subdistrict Sungai Kakap, Kuburaya District from November 12th 2017 to February   10th 2018. Methode used is Randomized Block Design (RBD) with 6 factors, there were A: Burangrang varieties, B: Anjasmoro varieties, C: Argomulyo varieties, D: Dena 1 varieties, E: Gema varieties and F: Dering 1 varieties. Each factor replicated four times, so there were 24 experimental units. Variables measured were plant height, root volume, number of effective root nodules, dry weight of plants, number of chlorophyll, flowering age, harvest age, number of productive branches, number of pods per plant, number of seeds per pod, dry weight of 100 seed, dry weight of seed per plot. The result showed that morphophysiology response   of some soybean varieties in the tidal land type C indicates a difference on number of effective root nodules, number of chlorophyll, flowering age , harvest age, number of pods per plant, number of seeds per pod, dry weight of 100 seed and dry weight of seed per plot.